Implementation of PRINCE algorithm in FPGA - Abbas Y.A.; Jidin R.; Jamil N.; Z'aba M.R.; Rusli M.E.; Tariq B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Algorithms; Application programs; Cryptography; Field programmable gate arrays (FPGA); Hardware; Hardware security; High speed cameras; Integrated circuit design; Logic Synthesis; Security of data; Throughput; Architectural modeling; Block ciphers; Cryptographic algorithms; Hardware implementations; PRINCE; Software implementation; Very high speed integrated circuits; VHDL; Computer hardware description languages